PEMBINAAN POLA HIDUP SEHAT “CERDIK” PADA LANSIA RISIKO DAN HIPERTENSI DI KELURAHAN PAJAJARAN KOTA BANDUNG - Supriadi Supriadi; Achmad Husni (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
Hypertension has killed 9.4 people worldwide every year. WHO estimates that the number of people with hypertension will continue to increase along with the growing population. In 2025, it is projected that around 29% of the world's population is affected by hypertension and currently the highest percentage is in developing countries. In Southeast Asia, 36% of adults suffer from hypertension. High blood pressure can be prevented by changing your lifestyle. The Ministry of Health seeks to increase self-awareness through the activities of the integrated non-communicable disease development post (Pos Bindu PTM). People are invited to behave smart, namely regular health checks, getting rid of cigarette smoke and other air pollution, diligent physical activity, healthy diet with balanced calories, adequate rest, and managing stress. The public can also know the risk factors, detection, treatment, and management of hypertension emergency response. In this regard, the Health Polytechnic of the Ministry of Health Bandung contributes to efforts to prevent and manage hypertension clients, so that their quality of life is better, namely through science and technology development programs for the community or community service as one of the three dharmas of higher education. After fostering a "CERDIK" healthy lifestyle, the elderly group at risk and hypertension increased their knowledge of the CERDIK healthy lifestyle, so that the elderly can enjoy their lives healthily. The method used is coaching through education. The results obtained Knowledge of elderly risk and hypertension about healthy lifestyle CERDIK mean score before coaching: 45.50 in RW 09 and 51.75 in RW 10, and the average score after coaching: 62.25 in RW 09 and 64.50 in RW 10. Outputs for fostering a "CERDIK" healthy lifestyle for the elderly at risk and hypertension in Posbindu, Pajajaran Village, Bandung City: a. elderly who do not have hypertension risk, and b. The elderly who had hypertension did not experience complications such as stroke or other disorders due to hypertension.